The Virtual Shoulder and Knee Physical Examination - Lamplot, Joseph D. (Orthop J Sports Med, 2020)
The COVID-19 crisis has forced a sudden and dramatic shift in the way that clinicians interact with their patients, from outpatient encounters to telehealth visits utilizing a variety of internet-based videoconferencing applications. Although many aspects of pre–COVID-19 outpatient sports medicine care will ultimately resume, it is likely that telehealth will persist because of its practicality and because of patient demand for access to efficient and convenient health care. Physical examination is widely considered a critical obstacle to a thorough evaluation of sports medicine patients during telehealth visits. However, a closer reflection suggests that a majority of the examination maneuvers are possible virtually with limited, if any, modifications. Thus, we provide a comprehensive shoulder and knee physical examination for sports medicine telehealth visits, including (1) verbal instructions in layman’s terms that can be provided to the patient before or read verbatim during the visit, (2) multimedia options (narrated videos and annotated presentations) of the shoulder and knee examination that can be provided to patients via screen-share options, and (3) a corresponding checklist to aid in documentation.